Relationship between pruritus and sleep in participants with primary biliary cholangitis in the Phase 2b GLIMMER trial - Robyn von Maltzahn; Marlyn J. Mayo; Helen T. Smith; April Thompson; Sugato Das; Andrea Ribeiro de Souza; Edoardo Lisi; Cynthia Levy; Megan M. McLaughlin; David Jones (SpringerOpen, 2024)
Abstract Background Cholestatic pruritus and fatigue are debilitating conditions associated with primary biliary cholangitis (PBC) and can significantly impact patients' quality of life. Pruritus in PBC often worsens at night and patients frequently report sleep disturbance, which contributes to cognitive symptoms and fatigue. Linerixibat is an ileal bile acid transporter inhibitor in clinical development for the treatment of pruritus associated with PBC and was recently assessed versus placebo in the Phase 2b GLIMMER trial. This post-hoc analysis assesses the relationship between pruritus severity and sleep disturbance in participants of GLIMMER regardless of treatment group. Methods GLIMMER (NCT02966834), a multicenter, double-blind, randomized, placebo-controlled trial, recruited 147 patients with PBC and moderate-to-severe pruritus. Following 4 weeks single-blind placebo, patients (randomized 3:1) received linerixibat or placebo for 12 weeks (to Week 16). Participants graded their itch (twice daily) and its interference with sleep (once daily) in an electronic diary using a 0-10 numerical rating scale (NRS). Weekly and monthly itch scores were calculated as the mean of the worst daily itch score over the respective time period. At study visits, participants completed the 5-D itch scale and the PBC-40 quality of life questionnaire, both of which contain an item specific to itch-related sleep disturbance. The impact of pruritus on sleep was assessed post hoc through correlations between the changes in NRS, 5-D itch, and PBC-40. Results Strong correlations were found between change from baseline in weekly itch and sleep NRS scores (r = 0.88 [95% confidence interval (CI): 0.83; 0.91]) at the end of treatment (Week 16), as well as in monthly itch and sleep NRS scores (r = 0.84 [95% CI: 0.80; 0.87]). Patients with improved weekly pruritus score severity category demonstrated reduced perceived sleep interference on average. Itch responders (≥2-point improvement in weekly itch score from baseline) displayed larger improvements in weekly sleep NRS score, 5-D itch, and PBC-40 sleep items, than itch non-responders (<2-point improvement). Conclusions A strong correlation exists between changes in pruritus severity and sleep interference in patients with PBC; pruritus reduction could generate concomitant improvement in sleep.